Introduction: hyper-visuality: images in the era of social platforms, digital archives and computational economies - D’Armenio, Enzo; Dondero, Maria Giulia (Visual communication (London, England), 2024)
Images are today at the centre of multiple social and technological tensions as a consequence of the adoption of digital coding, of the massive diffusion of social networks and of the algorithmic processing to which they are subject, resulting in new opportunities for developing analytical inquiries and meaning-producing social actions. In this introduction, the authors intend to reconstruct the broad context that makes images one of the most important resources of the digital era and to focus on some of the research tracks that characterize it. In the first part, they begin by focusing on the relationship between images and the digital, which they retrace in accordance with the selection of three key moments: the transition from ontology to the epistemology of digital media; the opening, by social networks and portable devices, of a field for the computational study of contemporary cultures; and, finally, the analytical potential arising from the encounter between digital archives and computer algorithms. In the second part, they present the three axes around which this issue is structured: archives, identity and algorithms. They first of all discuss the concept of the archive, by presenting four different understandings it has come to bear in conjunction with digital encoding – the archive as heritage, resource, effect and as database. They go on to address the relation between images and identities, arguing that social platforms and visual apps are a new domain for identity experimentation and social aggregation. Finally, they discuss the issue of algorithms and more generally of the new computational economy that associates large amounts of data with their mobilization as operational images.